Aspectos clínicos e epidemiológicos da placa aural em equinos no estado de Minas Gerais - Rodrigues, Gabryele Gomidy (2023)
Aural plaque is a dermatological disease that affects the pinna of the equines, causing punctiform or coalescent injuries characterized by depigmentation and keratinization. The association between these injuries, the viral types that causes the disease and the different breeds of equines are poorly described. The objective of this study was to determine the clinical prevalence of aural plaques in equines of the Mangalarga Marchador (MM) and Quarter Horse (QH) breeds in the state of Minas Gerais, evaluating the association of this prevalence with some risk factors, and to detect the presence of Equus caballus papillomavirus (EcPV) DNA in aural plaque biopsies, correlating with ear injuries characteristics. 400 MM horses and 425 QH horses of different ages, gender, coats, functions and management were clinically evaluated. Biopsies of injuries from 30 equines were performed. 15 of each breed. They were processed and submitted to the PCR technique, using previously described primers for EcPVs 1-9. In about 41,5% and 33.6% of the MM and QH were detected aural plaques, respectively. MM horses aged from 1 to 5 year old, showed a higher frequency of AP than QH horses, besides a higher sensibility with touch and bigger sensibility to infection with existance of ectoparasites. Among the samples, 90% were positive for at least one viral type, with the most frequent papillomavirus in both breeds being EcPV 4, present in 60% of the animals (20% in QH and 40% in MM), followed by EcPV6 53.3% (16.6% in QH and 36.7% in MM), EcPV5 13.3% (10% in QH and 3.3% in MM), EcPV3 13.3% (6.6% in QH and 6.6% in MM) and EcPV1 10% (3.3% in QH and 6.7% in MM). In one sample, there was isolated detection of EcPV1, previously described only in co-infections. When evaluating the existence of co-infection of the different viruses, MM horses had a higher rate of co-infections compared to equines, with emphasis on the association of EcPVs 4 and 6. It is concluded that the aural plaque is widely distributed in the state of Minas Gerais, with a higher prevalence of EcPV4, and MM equines have a higher susceptibility and frequency of the disease compared to QH equines. The lack of detection of EcPVs 2, 7, 8 and 9 suggests that they are not associated with aural plaque in this state of the country.